Utilização de resíduo do desempoeiramento do alto forno para tratamento de efluentes - Camila Costa de Amorim (2010)
The use of the blast furnace dust (BFD) for wastewater treatment by adsorption, Fenton-like and heterogeneous Fenton processes, besides the removal of Cr (VI), and the incorporation of tar was subjects of this work. The results of the BFD characterization indicated a low surfacearea (3.3 m2.g-1) with predominance of macropores, and morphological features with groups formed with clusters formed with iron spherical particles and carbon. The X-ray diffraction revealed the presence of hematite and magnetite in the BFD, confirmed by Mössbauer spectra.Tests of adsorption of dyes RR 195 and RY145 in BDF showed a low efficiency of adsorption, requiring high doses of waste (120 g/L) and contact time of 30 hours at pH 3.0 for complete decolorization and TOC removal of 100%. The adsorption of both dyes in BDF followed the kinetic model pseudo second order, with isotherms of Langmuir (RY145) andBET (RR195). Reuse and regeneration of BDF in the adsorption of dyes were able to achieve high efficiencies of discoloration (> 85%) and TOC (> 70%) by 3 cycles of use. The use of PAF as a source of iron, acid pH, the modified Fenton process, was able to remove 100% of the color of the dyes tested and about 40% of TOC and also presented a decrease ofaromaticity. With respect to the modification of the PAF for application in heterogeneous Fenton, the RTP analysis indicated that the iron oxides present in the PAF are somehow encapsulated by carbon in the sample. Heat treatment of PAF in N2, at temperatures of 400, 600 and 800 °C for 1 hour and 800 ° C for 2 hours, were not successful in changing the phases of iron oxide, or even the heterogeneous Fenton. The reduction of PAF in H2, at temperatures of 400, 600, and 800 º C for 2 hours and up to 700 ° C, was able to modify the phases of iron oxides present in the PAF, leading to formation of metallic iron in all materials, allowing some activity in the heterogeneous Fenton and the reduction of Cr (VI). The TOCanalysis indicated the reductive degradation of the dye in the presence of PAF_800H. The incorporation of tar pitch in PAF treated at 400, 600 and 800 °C, N2, allowed the reduction of iron oxide, obtaining an active material for the oxidation of RR195 and reduction of Cr (VI).